Upaya Mendorong Kolaborasi menuju Pengembangan Struktur Ruang Bernuansa Knowledge Based di Era Disrupsi - Ridwan Sutriadi; Ahmad Zaini Miftah (Diponegoro University, 2020)
This paper explores the development of multi centre urban spatial structures, as the development of three classical models, namely monocentric, sectoral, and multiple nuclei. By implementing a literature study method on studies of the global development of urban spatial structures which began from the 1960s until the 2000s era, lessons learned for Indonesia can be taken in promoting sustainable urban spatial structure. The thought of developing urban spatial structure starts from the awareness of urban expansion beyond its administrative boundaries in the 1960s (urban field), the importance of the systemic context in the development of urban spatial structures (1970s), the systemic concept must be supported by the collaboration of mutual cooperation among city’s functions in the concept of inter-city networks (1980s), spatial planning integration between core cities and suburbs which emerge urban areas (1990s). In 2000s era, the development of polycentric could be located in one urban area or among urban areas, also highly connected with innovation as a reflection of the use of knowledge for urban centers (2010s era). During the decades, it can be concluded that multi city centers lead to the enrichment of urban function in the sense of public interest and common concern, especially symbolizes continuing knowledge based innovation which could interfere market and existing values (disruption era), so collaboration among city centers is needed to perform a sustainable synergic urban spatial structure.